Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Our platform offers a seamless experience for finding reliable answers from a network of experienced professionals. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
(N-7)(n+2)=0 as you'd get n^2-7n+2n-14 then just simplify. Then it would be n=-2 or 7
[tex]n^2-5n-14=0 \\
n^2-7n+2n-14=0\\
n(n-7)+2(n-7)=0\\
(n+2)(n-7)=0\\
n=-2 \vee n=7[/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.